2019
DOI: 10.1074/jbc.ra118.005103
|View full text |Cite
|
Sign up to set email alerts
|

Bile acid analogues are activators of pyrin inflammasome

Abstract: Bile acids are critical metabolites in the gastrointestinal tract and contribute to maintaining intestinal immune homeostasis through cross-talk with the gut microbiota. The conversion of bile acids by the gut microbiome is now recognized as a factor affecting both host metabolism and immune responses, but its physiological roles remain unclear. We conducted a screen for microbiome metabolites that would function as inflammasome activators and herein report the identification of 12-oxo-lithocholic acid (BAA485… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 42 publications
0
40
0
1
Order By: Relevance
“…Recently, studies found that bacterial toxins can modify the Switch-I region of RhoA and trigger pyrin activation, such as TcdA and TcdB secreted from Clostridium difficile 27 . Additionally, a most recent study demonstrated that bile acid analogs of microbial origin, such as BAA473 and BAA485, can also activate the pyrin inflammasome 28 . NLRP3 inflammasome is triggered by numerous stimuli, including endogenous molecules, crystalline substances, pathogenic microbes, and ATP.…”
Section: Inflammasome Familymentioning
confidence: 99%
“…Recently, studies found that bacterial toxins can modify the Switch-I region of RhoA and trigger pyrin activation, such as TcdA and TcdB secreted from Clostridium difficile 27 . Additionally, a most recent study demonstrated that bile acid analogs of microbial origin, such as BAA473 and BAA485, can also activate the pyrin inflammasome 28 . NLRP3 inflammasome is triggered by numerous stimuli, including endogenous molecules, crystalline substances, pathogenic microbes, and ATP.…”
Section: Inflammasome Familymentioning
confidence: 99%
“…That being said, inflammasome signaling is indeed essential for recovery from acute CDI, as complete abolishment of the inflammasome complex in ASC -/mice or inhibition of caspase-1 in vivo causes severe mortality during infection, higher bacterial burden, and impaired CXCL1-mediated neutrophil chemotaxis [88,89]. When putative secondary bile acids are screened for inflammasome activity, 2 deoxycholic acid analogs cause IL-1β and IL-18 release from epithelial and myeloid cells via activation of the pyrin inflammasome [90]. Furthermore, another study demonstrated that multiple secondary and primary bile acids had dose-inhibitory activity on the NLRP3 inflammasome, with the secondary bile acid lithocholic acid having the greatest anti-IL-1β and caspase-1 inhibition [91].…”
Section: Fmt-restored Secondary Bile Acids Interact With Host Inflammmentioning
confidence: 99%
“…Cultivation of organoids derived from pluripotent or tissue-specific stem cells may help to more realistically assess the behaviour of cells capable of assembling inflammasomes in the context of their complex tissue environment and architecture (Rios & Clevers, 2018). This was, for example, shown for intestinal organoids recapitulating the four major cell types of the intestinal epithelium, enterocytes, goblet cells, Paneth cells and enteroendocrine cells, in which inflammasome-dependent IL-18 secretion after stimulation of NLRC4 (Rauch et al 2017), NLRP9 (Zhu et al 2017) and pyrin (Alimov et al 2019) inflammasomes was investigated. Importantly, quantifying the mere expression levels of inflammasome components under steady state conditions will not be sufficient to identify the relevant cell types that assemble inflammasomes, as expression may only be upregulated in response to other cytokines or in the context of infection.…”
Section: Microscopic Detection Of Inflammasomes In Tissuesmentioning
confidence: 99%